Essentialism in the Categories - Shapiro, Gabriel (Phronesis, 2023)
According to the Categories, predicates can be ‘said of’ their subjects or they can be ‘present in’ their subjects. The said-of relation has received relatively little scholarly attention, and scholars disagree on the answers to four foundational questions about the relation. (i) What is it? (ii) Is it an essential relation? (iii) How is it related to predication? (iv) Is it primitive? I argue that A is said-of B just in case A is a formal part of B. On this account, said-of is an essential relation and it is definable, but it is not defined in terms of predication.